Efficacy of preladenant in improving motor symptoms in Parkinson's disease: A systematic review and meta-analysis - Mohammad Amin Karimi; Alireza Ghajari; Reza Khademi; Mohammad Hossein Etemadi; Narges Safar Firouz; Behnaz Mohammadvand; Kimia Janeshin; Afra Darvishi; Shafagh Asgarzadeh; Sayedeh-Fatemeh Sadat-Madani; Mohammad Abbasalizadeh; Zahra Jafari Shendi; et al. (IBRO Neuroscience Reports, 2024)
Background: Parkinson's disease (PD) is a complex neurodegenerative disorder characterized by dopamine depletion and severe motor impairments. Preladenant, an adenosine A2 receptor antagonist, is an investigational treatment for PD. This systematic review and meta-analysis aimed to critically evaluate the efficacy of Preladenant in improving motor symptoms in patients with PD. Methods: A comprehensive literature search was conducted in PubMed, Embase, and Cochrane Central Register of Controlled Trials from inception to March 2023, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomized controlled trials (RCTs) comparing Preladenant with placebo in PD patients were included. The primary outcome was the change in daily ON time without troublesome dyskinesia. Secondary outcomes included the change in daily OFF time and adverse events. The risk of bias was assessed using the Cochrane Risk of Bias tool. Results: Four RCTs with a total of 2097 PD patients were included. Pooled analysis showed that Preladenant could generally increase daily ON time (pooled effect 0.15 and 95 % CI: −0.19–0.48) and reduce daily OFF time (pooled effect −0.04 and 95 % CI: −0.43–0.36) compared to placebo, however it was not significant. The included studies had moderate to high heterogeneity. No significant differences in adverse events were observed between Preladenant and placebo. Conclusion: This meta-analysis suggests that Preladenant may improve motor fluctuations in PD patients by increasing ON time and reducing OFF time. However, the high heterogeneity among studies warrants further large-scale, high-quality RCTs to confirm these findings and establish the long-term safety and efficacy of Preladenant in PD management.